(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to reveal teachers’ opinions about the usage of educational games in mathematics teaching: it investigates the impact of teaching mathematics with a learning-by-play strategy on acquiring mathematical skills and improving social communication skills among 6th-grade students in Israel. The study sample consisted of two divisions for the 6th -grade from Arab Schools in North Israel. Each of the two groups is consisting of 20 male and female students. One is studying using the traditional method and the other studying mathematics with a learning strategy by playing. The researchers developed the mathematical skills test and the social communication scale. There were statistically significant differences (α ≥ 05.0) between the mean averages of the two groups’ scores on the mathematical skills test and on the social communication dimension scale from the teacher’s viewpoint and the experimental group. In conclusion, the teachers indicated that educational computer games would provide benefits such as making students’ learning more permanent, visualizing concepts, making students love mathematics, learning by entertaining, reinforcing what has been discovered, and developing thinking skills. Nevertheless, the teachers stated the limitations of educational computer games, such as causing addiction and physical damages, being time-consuming, requiring special equipment and software, and making class management difficult. Besides, it was revealed that the teachers demonstrated positive attitudes towards the use of games in courses while they did not feel competent in terms of application. In this case study, one of the qualitative research methods was used. Data were collected by utilizing a semi-structured interview form with the teachers and analyzed using by content analysis method.